2017
DOI: 10.1007/s41247-017-0030-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Farm-Gate Life Cycle Assessment of Oilseed Feedstocks in the Northern Great Plains

Abstract: to perform well in southeastern South Dakota, canola performed well in northeastern North Dakota, and camelina and carinata remained strong alternatives comparatively across the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…[31]. A CED of 15.3 GJ/ha was reported for canola cultivated in the USA, with nitrogen input of 77.3 kg N/t seeds [32]. The energy demand of 5.3 GJ per t of rapeseeds was reported for Chilean conditions [33].…”
Section: Ced Methodsmentioning
confidence: 99%
“…[31]. A CED of 15.3 GJ/ha was reported for canola cultivated in the USA, with nitrogen input of 77.3 kg N/t seeds [32]. The energy demand of 5.3 GJ per t of rapeseeds was reported for Chilean conditions [33].…”
Section: Ced Methodsmentioning
confidence: 99%
“…Nemecek et al (2011) conducted a study to assess the LCA of farming systems in Switzerland and revealed that N2O and CO2 emitted from fertilizers and fossil fuels had the greatest impacts on GWP, respectively. In similar surveys on the LCA of soybean production in different parts of the world such as Northern Great Plains, USA (Moeller et al 2017), U.S. Midwest (Romeiko et al 2020b), Southern Brazil (Zortea et al 2018, Mato Grosso State, Brazil (Raucci et al 2015), and Jilin Province, China (Knudsen et al 2010) the amounts of CO2-eq emitted were reported 602 g kg -1 , -11.4 to 22 kg kg -1 , 0.734 kg kg -1 , 0.186 kg kg -1 , and 263 kg ton -1 , respectively. Although the GHG emission in different agro-ecosystems varies depending on climatic and soil conditions, the type of management practices also has a significant effect on the amount of these emissions and their environmental impacts.…”
Section: Climate Changementioning
confidence: 99%
“…Farming energy and fertilizer application rates were collected from Moeller et al (2017) and Sieverding et al (2016) that reflect carinata farming in northern United States and Canada. For oil extraction, we assume organic solvent (n-hexane) is used, and chemical and energy use are estimated based on Rispoli (2014).…”
Section: Carinata Hydroprocessed Esters and Fatty Acids (Hefa) Jet Fuel Productionmentioning
confidence: 99%